2007
DOI: 10.2174/092986707782023668
|View full text |Cite
|
Sign up to set email alerts
|

Onconeural Versus Paraneoplastic Antigens?

Abstract: A hallmark of naturally occurring tumor immunity is the aberrant expression of so called "onconeural antigens" or "paraneoplastic antigens". At present, these two terms are used as synonyms for proteins which are normally expressed only in neuronal tissues, but in the process of carcinogenesis, they can be detected in tumors located outside the nervous system. As neuronal tissues are immunopriveleged zones, expression of these proteins in tumor cells can induce an autoimmune response, which manifests in the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…The antibodies are often present in sera from patients suffering from neurological PNS [15], [21], [22]. Scientific evidence has shown that anti-Ma2 positive sera sometimes are associated with tumor diagnosis [15], [16], [23], [24].…”
Section: Introductionmentioning
confidence: 99%
“…The antibodies are often present in sera from patients suffering from neurological PNS [15], [21], [22]. Scientific evidence has shown that anti-Ma2 positive sera sometimes are associated with tumor diagnosis [15], [16], [23], [24].…”
Section: Introductionmentioning
confidence: 99%
“…Most paraneoplastic syndromes are considered to be autoimmune-mediated. The autoimmune responseresultsinthegenerationofspecificcytotoxicT-cells and autoantibodies that react with neural proteins and the causal tumor, so-called onconeural antigens [7,8]. Typical MRI findings of PLE include unilateral or bilateral mesial temporal lobe abnormalities that are best seen on T2-weighted images, but in 20% of the patients, as in our case, MRIfailstoshowchangeswithinthelimbicsystem [9].…”
Section: Discussionmentioning
confidence: 84%
“…2 To prove this hypothesis, we isolated splenocytes (as a source of both T and B cells) and serum (as a source of immunoglobulins) from tumor-bearing mice and adoptively transferred them into healthy mice. One quarter of the recipients showed retinal degenerations.…”
Section: Discussionmentioning
confidence: 99%